Diplomatic Representation of Lithuania in France During the 1940–1960 - Jonušauskas, Laurynas (Genocidas ir rezistencija, 2025)
In 1940, the Soviets by illegal means subordinated the embassy of Lithuania in Paris, and thus, Lithuanian diplomats were placed in an ambiguous situation. After the Soviets had arrested the Lithuanian envoy Petras Klimas, French authorities agreed for semi-official and subtle representation of Lithuania by Dr. Stasys Antanas Bačkis. Despite the unfavourable conditions the new envoy did much handling the problems of Lithuanian refugees and students. In addition to his activities in France, Bačkis very actively participated in joint projects of the diplomats of Baltic States, in different international and Lithuanian political organisations, and contributed much disseminating information about Lithuania to the West. Dr. Bačkis continued his representation of Lithuania in France till he, in 1960, was appointed to the embassy of Lithuania in Washington.
Keywords: Soviet occupation; diplomacy; France; emigree